An observational study for evaluating prescription pattern of drugs, adverse drug reactions in paediatric acute lymphoid leukaemia in a tertiary care hospital - S., Kulkarni A.; C., Shetty Y.; G., Narula (International Journal of Research in Medical Sciences, 2024)
Background: Prescription research analyses trends in prescribing drugs as per rational therapeutics principles and if any deviations found helps in providing vital feedback to physicians. Recent advances in cancer chemotherapy has improved survival rates in Acute Lymphoblastic Leukaemia (ALL), but the adverse drug reactions adds to disease burden, also compromises quality of life. There is paucity of data on prescription audit, adverse drug reactions in paediatric ALL, hence the study was planned. Methods: Study was cross-sectional prospective audit. After IEC approval, written informed consent were taken from 156 prospective ALL patients aged 1-15 years (completed one cycle of induction phase). The variables assessed were WHO prescribing indicators, completeness. The details of adverse drug reactions-type, severity, preventable; causality assessment (WHO-UMC, Naranjo Scales). Analyzed by descriptive statistics [Microsoft Excelv16.0]. Results: Out of total 156 prescriptions (2576 drugs prescribed), total drugs per prescription was 16. Most of the drugs were prescribed by generic name (97.94%). Commonest anticancer drug prescribed in regimen was vincristine, methotrexate. Most common supportive medication class were antiemetic, antacid, antiulcer. 100% prescriptions were complete for anticancer drugs, 66% for supportive care medications. Most common ADR found was alopecia (100%), febrile neutropenia (31.41%) and fatigue (30.76%). Majority ADR were possibly (93.81%) related to treatment. 37.97% ADR were of moderate severity, 100% ADRs were not preventable. Conclusions: The commonest anti-cancer drugs prescribed are vincristine, methotrexate and supportive care prescribed is antiemetic therapy (granisetron). The frequent adverse drug reaction found was alopecia, febrile neutropenia.